Estimasi Model Perubahan Indeks Harga Saham Gabungan melalui Regresi Kuantil Spline Smoothing - Ashwad K, Hajratul; Islamiyati, Anna; Siswanto, Siswanto (Hasanuddin University, 2025)
Regression of nonparametric quantile is conducted on purpose to help estimating the function of regression when the assumptions about the regression curve shape are not known involving quantile values. Spline is claimed as one of the estimators commonly applied in nonparametric regression. Patterns of platelet change in Jacarta Composite Indeks (JCI) based on Dow Jones Index (IDJ) were analyszed by quantile spline smoothing using τ 0.25, 0.50, and 0.75. The analysis results show two patterns of change in the relationship of JCI and the IDJ. It can be seen from the optimal knot point for each quantile, namely 28500, 35000 and 29600, which shows that before and after the IDJ value reaches the point from the knot point, there is a tendency to decrease and then increase in the JCI data. The optimal model with the one-knot point. According to the minimum GCV value, the optimal model with the smallest GCV vaue, which is 5243.45 on quantile 0.75.